Entrepreneurship Education, Entrepreneurial Competence, Business Strategy, and Technology Access as Determinants of MSME Success in West Nusa Tenggara, Indonesia - Muh Fahrurrozi; Yuni Artika; Pahrudin Pahrudin (Sumber Belajar Sejahtera, 2026)
Micro, small, and medium enterprises (MSMEs) play a strategic role in fostering employment, economic growth, and community welfare. However, many MSMEs in developing regions continue to face challenges related to limited entrepreneurial education, insufficient competence, weak business strategies, and suboptimal utilization of technology. This study aims to analyze the influence of entrepreneurship education, entrepreneurial competence, business strategy, and technology access on MSME success in West Nusa Tenggara, Indonesia. This research applied a quantitative explanatory survey design with a total sample of 204 MSME owners selected through simple random sampling. Data were collected through questionnaires and Google Forms and analyzed using multiple linear regression. Findings reveal that entrepreneurship education, competence, business strategy, and technology access significantly and positively affect MSME success, both partially and simultaneously. These results highlight the importance of strengthening human capital development, strategic orientation, and digital adoption to improve MSME performance and sustainability. The study contributes to the growing literature on MSME development and provides practical insights for policymakers and business practitioners to formulate effective empowerment strategies.